Design and Construction of High-Quality Capacitor for High Frequency and Power Application - Martin Zavřel; Vladimír Kindl; Tomáš Kavalír; Pavel Drábek (Communications - Scientific letters of the University of Zilina, 2021)
The paper proposes a design and construction of a special plated capacitor exhibiting very good high-frequency characteristics. The capacitor is designed to minimize the parasitic parameters like ESR (equivalent series resistance) and ESL (equivalent series inductance) and to be suitable for power industry applications. The paper describes the fabrication process and discusses technical issues related to technology of manufacturing and assembling. It also provides an experimental verification and the quality evaluation based on frequency characteristics compared to existing commercial high-quality capacitor.